PERANAN PERADILAN PERIKANAN DALAM KASUS PENCURIAN IKAN DI WILAYAH KEPULAUAN RIAU - Tuah Kalti Takwa; Erdianto '; Lady Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Geographical condition of Indonesia as a country that two-thirds of marine waters is composed of marine coastal seas, sea bays and straits give Indonesia the abundant riches, in terms of want to keep and preserve natural resources and biodiversity it is necessary judicial fisheries as one efforts to combat illegal fishing that occurs in the region of Riau Islands. Based on this understanding, the authors of this paper formulated the three formulation of the problem, namely: first, how the judicial role of fisheries in the theft of fish that occur in the Riau Islands? second, what are the barriers faced in overcoming the judicial fishery poaching in the Riau Islands? third, whether the efforts made by the judiciary in addressing illegal fishing fisheries that occur in the Riau Islands?The research method in this study, first, this kind of research is legal juridical sociology because in this study the authors directly conduct research on location or place ditelitit to provide complete and clear picture of the issues researched, the study was conducted in the District Court Cape nut, while the sample population was a total party related to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary data collection techniques in this study by observation, interview, and literature study.From the research, there are three main things that can be inferred. First, that Indonesia is very serious in combating illegal fishing that occur in Indonesia. by following the Law No. 45 of 2009, the Fisheries Justice in this case the judicial role of fisheries has contributed greatly to the handling of cases that continues for all cases of illegal fishing. Second, barriers encountered in the judicial role of fisheries in the case of illegal fishing in the area is Riau Islands, the lack of human resources in terms of number and quantity, the amount of which is owned by their respective regulatory agencies, are still limited means of infrastructures and budgets, yet orderly licensing that provides opportunities the occurrence of forgery permission. Third, the efforts made by the judicial fisheries in the case of illegal fishing in the Riau archipelago budget increase for supervisors and law enforcement agencies, conducted socialization to the community, the Act is to be synchronized, modernization of fishing vessels, vessel license restrictions. First author's suggestion to the court by the fisheries Act that have not been synchronized to remain steadfast in their duties, the Second to the ministry of marine fisheries and water police to be more assertive in the taskKeywords : Role - Justice Fishing - Fish Theft